Green Nanomedicine & its Therapeutic Potential - Dwivedi, Shambhavi; PRAJAPATI, MANSI; Purohit, Gunjan (RSYN Proceedings, 2025)
This literature survey/review article examines recent advancements in sustainable methods for synthesizing green nanoparticles and evaluates their effectiveness in therapeutic applications. Nanoparticles are materials engineered at the nanoscale—typically within the range of 1–100 nm—where their extremely small size imparts unique chemical, physical, magnetic, and electronic properties to various metals and non-metals. Conventional industrial synthesis of nanoparticles often relies on toxic chemicals, raising significant environmental and biological safety concerns. To address these limitations, green nanotechnology has emerged as a sustainable approach that minimizes the use of hazardous substances in the production of metallic and non-metallic nanomaterials. The green synthesis of nanoparticles using plants, microorganisms, and biopolymers not only eliminates toxic reagents but also enhances cost-effectiveness, biocompatibility, and eco-friendliness. Green nanomaterials demonstrate remarkable therapeutic potential, showing efficacy in cancer treatment, antimicrobial and antiviral therapies, anti-inflammatory applications, immunomodulation, and regenerative medicine. Despite these promising biomedical applications, the translation of nanomaterials into clinical practice faces challenges, including safety validation, ethical considerations, and regulatory approval processes. This review explores recent innovations in sustainable nanoparticle synthesis and critically assesses their potential and limitations in therapeutic applications